Gender differences in the factors associated with early age of initiation of cannabis use in Jamaica. (4th March 2019) - Oshi, D. C.; Ricketts-Roomes, T.; Oshi, S. N.; Mitchell, C.; Agu, C. F.; Belinfante, A.; Mitchell, G.; Whitehorne-Smith, P.; Harrison, Joy; Atkinson, U.; Abel, W. D.
ABSTRACT: Objective: This study aimed to examine the gender differences in the factors associated with early age of cannabis use. Methods: Secondary data analysis was done on the National Housing Survey 2016. Descriptive statistics consisted of computation of sociodemographic characteristics and Pearson's Chi Square. Multivariate analysis of factors associated with age of debut of cannabis use was done using binary logistic regression. Results: Of the 4, 623 participants, 54.8% were females. The mean age of initiation (AOI) of cannabis use for the sample was 16.89 years (standard deviation [SD]: 5.06); males 16.03 years (SD: 4.39), and females 18.96 years (SD: 5.92). Male Rastafarians, but not females, had higher odds of early cannabis use debut compared to those who have no religion adjusted odds ratio (AOR): 2.33, 95% confidence interval [CI]: 1.04–5.19). Married as well as single females, but not males, were significantly less likely to have had early cannabis use debut compared to the divorced/separated ones (AOR: 0.06, 95% CI: 0.01–0.53; AOR: 0.08, 95% CI: 0.01–0.73, respectively). There was a significant positive association between primary/lower educational level and early AOI for females (AOI: 4.48, 95% CI: 1.51–15.20), but not for males. Conclusion: There were significant gender differences in the factors associated with early initiation of cannabis use in the Jamaican population.